Assessment of Fish Vending Parameters in Sta. Rosa Wet Market - Chavez, Sabrina Cheyenne E. (Animo Repository, 2022)
The diversity of the fishes in the Philippines is massive considering the fact that the Philippines is known as one of the major fish producers in the world. Knowing this, it is difficult to manage and protect marine biodiversity in order to maintain the quality of the fish being sold to the people. This study aims to identify different fish stock data collected from the Santa Rosa Wet Market from December 2021 to February 2022, correlate the data, and compare the results with the previous studies. The study adopted the research designs and the pre-made questionnaires of related previous studies, and these questionnaires were given to the fish vendors working in the specified wet market. In analyzing the data, the researchers used Pearson’s correlation coefficient to assess the factor’s correlation with each other. From the months of December to February there have been significant changes in fish parameter relationships. Noting that these months are also filled with holiday seasons where demand for fish is high, parameters such as length and price have noticeably increased with one another. Although after the onset of the new year, the price and length have noticeably shown an inverse relationship as the seasonal events come to a close. Eventful months of the year have placed a huge direct relationship impact on the fish vending parameters concerning length and price.